Mycoses in otorhinolaryngology: diagnostics, prevention, therapy - K. V. Eremeeva (Медицинский совет, 2016)
The article provides data on diagnostics and tactics of patient management with external otitis especially of mycetogenic etiology (otomycosis). Possibiities of combined topical four-component drug Candibiotiс and its universal effect combining antibac-t erial, antifungal, anti-inflammatory and analgesic actions. An experience of application of Candibiotic has been shown in Russia in the recent 10 years, by results of studies its effectiveness in therapy of acute and chronic inflammatory diseases of the middle and external ear is provided, including otomycosis.